2018
DOI: 10.1186/s13063-018-3058-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of polydioxanone thread embedded at specific acupoints for non-specific chronic neck pain: a study protocol for a randomized, subject-assessor-blinded, sham-controlled pilot trial

Abstract: BackgroundThis study aims to evaluate the efficacy and safety of thread-embedding acupuncture (TEA) with polydioxanone thread embedded at various acupoints, compared with sham TEA, for the treatment of non-specific chronic neck pain.Methods/designThis study will be an 8-week-long, two-armed, parallel, randomized, subject-assessor-blinded, sham-controlled pilot trial. Fifty eligible patients will be randomly allocated into the real TEA group or the sham TEA group. The real TEA group will receive TEA treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…TEA was administered once weekly, whereas PT twice weekly because this study focused on verifying external validity based on actual clinical practice as well as treatment frequency of TEA and PT in previous studies. 15 , 16 , 57 Nevertheless, it was noteworthy that fewer sessions of TEA yielded better outcomes than PT. The therapeutic mechanism of TEA has yet to be clearly established; however, it is suggested that long-lasting stimulation of afferent fibers by embedded PDO threads contributes to pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…TEA was administered once weekly, whereas PT twice weekly because this study focused on verifying external validity based on actual clinical practice as well as treatment frequency of TEA and PT in previous studies. 15 , 16 , 57 Nevertheless, it was noteworthy that fewer sessions of TEA yielded better outcomes than PT. The therapeutic mechanism of TEA has yet to be clearly established; however, it is suggested that long-lasting stimulation of afferent fibers by embedded PDO threads contributes to pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…This trial is designed to compare the clinical effectiveness and safety of TEA with that of PT in the treatment of patients with CNP. Although TEA treatment studies for CNP have been reported, [14,15] to the best of our knowledge, no RCT investigating the effectiveness and safety of the TEA treatment compared with PT in the treatment of patients with CNP has been reported. Therefore in this trial, we will set the PT group as a control group to evaluate the differences in therapeutic effects caused by the TEA.…”
Section: Discussionmentioning
confidence: 99%
“…This study is to recruit 128 applicants, who meet the criteria of inclusion and exclusion (Table 1). [14,15,21] A total of 128 patients with CNP are to be recruited from Daejeon University Dunsan Korean Medicine Hospital. Applicants will be recruited through advertisements posted on bulletin boards at hospitals, subway stations, apartments, subway cars, hospital homepages, newspapers, etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] Thread embedding treatment maximizes stimulation by inserting embedded threads into the acupoint, percutaneous layer, superficial muscles, meridian system, or areas that induce pain by means of needle retention action. [ 12 ] In addition, it activates the meridian system, supply nutrients to muscles and peripheral nerves, and strengthening cell immunity. [ 13 , 14 ]…”
Section: Introductionmentioning
confidence: 99%